La isla del tesoro - Stevenson, Robert Louis, 1850-1894 (Colección Biblioteca nueva de aventuras ;, 2013)
While going through the possessions of a deceased guest who owed them money, the mistress of the inn and her son find a treasure map that leads them to a pirate's fortune.